Framework for harm elimination in light of the Islamic legal maxims - Muhsin, Sayyed Mohamed; Amanullah, Muhammad Amanullah; Zakariyah, Luqman (Islamic Cultural Centre, London., 2019)
Islamic legal maxims (qawāʿʿid fiqhiyyah) provide necessary basis for extracting legal injunctions on the unprecedented cases (fiqh al-nawāzil) and make it possible for the jurists to forego the need of memorizing copious fiqh treatises. In light of this fact, this article attempts to design a framework for harm elimination, utilizing the related legal maxims, which will be arguably of great use in developing an outlook that enables a person to tackle the many challenges he or she finds in the course of removal of harm. After explaining the concept and definition of Islamic legal maxims in general, this research surveys in detail the universal legal maxim “harm must be eliminated”, covering its role and significance in the theories of fiqh and its scope and application in contemporary issues. Employing descriptive, analytical and critical methods, this study categorizes the legal maxims related to the harm elimination into three: (1) maxims related to prevention of harm before its occurrence, (2) maxims related to elimination of harm after it has taken place and (3) maxims related to minimization of harm if complete removal is impractical. Likewise, this research analyses the sub-maxims of harm elimination, discussing their legal bases, various purposes for which they operate, related uṣūlī principles and legal examples, providing at the end a flowchart that represents a sequence of five steps useful in the course of removal of harm